Analisis Pemahaman Laba, Penentuan Laba Optimal, dan Pengelolaan Keuangan pada Sektor Informal (Studi Fenomenologi pada Pedagang Kaki Lima di Taman Akcaya Pontianak) - Laire, Wahyu Laksana Caesar (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to analyze profit understanding, optimal profit determination, and financial management among street vendors in Taman Akcaya Pontianak. This research employs a qualitative method with a phenomenological approach. Data were collected through interviews, observations, and documentation involving six street vendors operating in Taman Akcaya Pontianak. The results show that most street vendors do not understand profit theoretically, either from the perspective of conventional profit concepts or basic accounting profit. Their understanding of profit is mainly based on practical experience, daily operations, and the difference between sales revenue and business capital. The study also finds that Cost-Volume-Profit analysis can be used as an appropriate method to determine optimal profit because it helps measure the relationship between cost, sales volume, selling price, and profit targets. However, the financial management practices of street vendors remain limited. Most informants have not implemented proper financial planning, routine financial recording, financial reporting, or financial control. The main obstacles include limited business capital, dependence on daily income, the inability to separate personal and business funds, the absence of cash reserves, limited financial knowledge, and reliance on traditional memory-based recording.